Effects of geotextile envelope and perforations on the performance of corrugated drain pipes - Yang, Haoyu; Wu, Jingwei; Guo, Chenyao; Li, Hang; Wu, Zhe (International Journal of Agricultural and Biological Engineering, 2023)
Subsurface drainage is an important agriculture drainage measure. It is primary to select suitable drain pipes and envelopes for efficient subsurface drainage. And now, corrugated drains and geotextile envelopes are widely used. However, the effects of geotextile envelopes and perforations on the drainage of corrugated drains are not well understood. This study conducted a series of sand tank experiments of steady-state flow with or without geotextile envelopes and with different perforation patterns. The drainage flow and the profile head distributions were analyzed and compared. Furthermore, the applicability of theoretical formulas, which are used to calculate effective radius considering the resistance of different perforation patterns, was evaluated. Results showed that the geotextile envelope weakened the effect of perforations on streamlines, thereby causing the value of effective radiuses to be close to that of the actual radius. The drainage flow of the drain with a geotextile envelope was six times that of the bare drain. The relationship between drainage flow and opening area could be described by inverse proportional function. Meanwhile, the drainage flow was affected by the perforation arrangement. Drain with small longitudinal perforation spacing had a drainage flow of approximately 15% larger than that with wider longitudinal perforation spacing. The bottom perforations drained out first and most, and the drainage flow of the drain opened at the bottom could be 11% higher than that at the top. Low-efficiency perforations cause higher head loss near the pipe wall. Existing formulas of entrance resistance were not suitable for geotextile-wrapped corrugated drains, the effect of geotextile envelope and orifice entrance loss at perforations should be considered.Keywords: geotextile envelope, perforation, corrugated drain, effective radius, drain opening, entrance resistance, drainage materialDOI: 10.25165/j.ijabe.20231601.7574Citation: Yang H Y, Wu J W, Guo C Y, Li H, Wu Z. Effects of geotextile envelope and perforations on the performance of corrugated drain pipes. Int J Agric & Biol Eng, 2023; 16(1): 36–44.